Root growth dynamics and biomass input of four over-wintering herbaceous crops in boreal conditions - Alakukku, Laura; Virkajärvi, Perttu; Kykkänen, Sanna; Pietola, Liisa (Scientific Agricultural Society of Finland, 2024)
Root growth of winter wheat (Triticum aestivum L.), winter rye (Secale cereale L.), red clover (Trifolium pratense L.), and timothy (Phleum pratense L.) was recorded to evaluate the environmental potential of over-wintering crops in a Nordic agroecosystem. In a field experiment on Aquic Haplocryoll soil, root intensities (number of roots/area) were measured to 50 cm depth by minirhizotron microvideo camera technology over a two -year period (21 recording sessions). At anthesis, root biomass and morphological parameters were measured by destructive soil sampling and image analysis of washed roots. Winter cereal roots reached 50 cm depth as soon as the autumn of the seeding year. For both post-seeding years, timothy roots developed the most intensively in spring, while red clover had higher root intensity than timothy in late autumn. At anthesis, the crops were ranked timothy > red clover > winter wheat > winter rye according to root length density, surface area density, and biomass. Based on S:R ratios, red clover appears to offer the most intense carbon sink at 0–60 cm soil depth. Over-wintering crops had living roots in the subsoil both in late autumn and early spring, indicating potential to plant available nutrient uptake outside the growing season of annual crops.
Keywords: Phleum pratense L.; Secale cereale L.; Trifolium pratense L.; Triticum aestivum L; minirhizotron; root bio-mass; shoot:root ratio